Exploring opportunities to prevent cirrhosis admissions in the emergency department: A multicenter multidisciplinary survey. Issue 3 (26th January 2018) - Siddique, Shazia Mehmood; Lane‐Fall, Meghan; McConnell, Matthew J.; Jakhete, Neha; Crismale, James; Porges, Stefanie; Khungar, Vandana; Mehta, Shivan J.; Goldberg, David; Li, Zhiping; Schiano, Thomas; Regan, Linda; et al.
Abstract : Patients with cirrhosis have high admission and readmission rates, and it is estimated that a quarter are potentially preventable. Little data are available regarding nonmedical factors impacting triage decisions in this patient population. This study sought to explore such factors as well as to determine provider perspectives on low‐acuity clinical presentations to the emergency department, including ascites and hepatic encephalopathy. A survey was distributed in four liver transplant centers to both emergency medicine and hepatology providers, who included attending physicians, house staff, and advanced practitioners; 196 surveys were returned (estimated response rate 50.6%). Emergency medicine providers identified several influential nonmedical factors impacting inpatient triage decisions, including input from a hepatologist (77.7%), inadequate patient access to outpatient specialty care (68.6%), and patient need for diagnostic testing for a procedure (65.6%). When given patient‐based scenarios of low‐acuity cases, such as ascites requiring paracentesis, only 7.0% believed patients should be hospitalized while 48.9% said these patients would be hospitalized at their institution ( P  < 0.0001). For mild hepatic encephalopathy, the comparable numbers were 19.5% and 55.2%, respectively ( P  < 0.001). Several perceived barriers were cited for this discrepancy, including limited resources both in the outpatient setting and emergency department. Most providers believed that an emergency department observation unit protocol would influence triage toward an emergency department observation unit visit instead of inpatient admission for both ascites requiring large volume paracentesis (83.2%) and mild hepatic encephalopathy (79.4%). Conclusion : Many nonmedical factors that influence inpatient triage for patients with cirrhosis could be targeted for quality improvement initiatives. In some scenarios, providers are limited by resource availability, which results in triage to an inpatient admission even when they believe this is not the most appropriate disposition. ( Hepatology Communications 2018;2:237‐244)